How Do Junior High School Students Utilize Interactional Strategies in Speaking Activity? - Hidayatul Avia; Yuli Astutik (Universitas Cokroaminoto Palopo, 2018)
Interactional strategies are very important especially for English as a foreign language learners which can help the learners negotiate of the meaning during the interaction in speaking activity. The aim of this research is to analyze the interactional strategies (ISs) utilized by three students at different levels (Low, Average, High) in speaking activity at the eighth grade students of SMP Islam As-Sakinah Sidoarjo. This research uses qualitative descriptive as a research design, which all of the data are obtained through observation and interview for three students at different level such as low level learner (LLL), average level learner (ALL) and high level learner (HLL). In brief, the results of this research show that LLL uses all aspects of interactional strategies in her speaking activity, average level learner (ALL) uses some aspects of interactional strategies and high level learner (HLL) almost never use the aspects of interactional strategies in his speaking activities.